2018
DOI: 10.1111/str.12281
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between uniaxial ratcheting and magnetic response under cyclic loadings in X80 pipeline steel

Abstract: The objective of this research is to explore the correlation between uniaxial ratcheting behaviour and magnetic response under asymmetrical cyclic stressing in X80 pipeline steel. The magnetic field variations from cycle to cycle were recorded simultaneously during ratcheting. Analysis made in the present work shows that the magnetic hysteresis loop evolves systematically with the number of cycles in terms of its shape and position. The most prominent result here is that the magnetic field under a certain stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Liu et al tested three components of the MMM signal, including B x , B y , and B z signals, corresponding to different fatigue cycles [21]. Bao et al studied the correlation between asymmetric cyclic stress and magnetic response of X80 pipeline steel and found that magnetic signals are more sensitive to the response of tensile stress [22]. Besides, He developed the Non-contact pipeline magneticbased stress inspection system based on weak magnetic stress detection technology to detect stress concentration in pipelines [23].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al tested three components of the MMM signal, including B x , B y , and B z signals, corresponding to different fatigue cycles [21]. Bao et al studied the correlation between asymmetric cyclic stress and magnetic response of X80 pipeline steel and found that magnetic signals are more sensitive to the response of tensile stress [22]. Besides, He developed the Non-contact pipeline magneticbased stress inspection system based on weak magnetic stress detection technology to detect stress concentration in pipelines [23].…”
Section: Introductionmentioning
confidence: 99%